2009
DOI: 10.1002/btpr.340
|View full text |Cite
|
Sign up to set email alerts
|

Separation of astaxanthin from cells of Phaffia rhodozyma using colloidal gas aphrons in a flotation column

Abstract: The aim of this study is to investigate the separation of astaxanthin from the cells of Phaffia rhodozyma using colloidal gas aphrons (CGA), which are surfactant stabilized microbubbles, in a flotation column. It was reported in previous studies that optimum recoveries are achieved at conditions that favor electrostatic interactions. Therefore, in this study, CGA generated from the cationic surfactant hexadecyl trimethyl ammonium bromide (CTAB) were applied to suspensions of cells pretreated with NaOH. The dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
0
4
0
2
Order By: Relevance
“…A surfactant-based separation technique, colloidal gas aphrons (CGA) has been previously studied in our group to recover various valuable bioactive compounds from 4 different feedstock such as astaxanthin (Dermiki, Bourquin, & Jauregi, 2010;Dermiki, Gordon, & Jauregi, 2009), proteins (Fuda & Jauregi, 2006;Fuda, Bhatia, Pyle, & Jauregi, 2005) and polyphenols (MohdMaidin, Michael, Oruna-Concha, & Jauregi, 2017;Spigno, Dermiki, Pastori, Casanova, & Jauregi, 2010;Spigno, Amendola, Dahmoune, & Jauregi, 2015). The type of surfactant (i.e cationic, anionic and non-ionic) determines the outer charge of the CGA, where molecules with the opposite charge will attract to the CGA resulting in their effective separation into the CGA phase.…”
Section: Introductionmentioning
confidence: 99%
“…A surfactant-based separation technique, colloidal gas aphrons (CGA) has been previously studied in our group to recover various valuable bioactive compounds from 4 different feedstock such as astaxanthin (Dermiki, Bourquin, & Jauregi, 2010;Dermiki, Gordon, & Jauregi, 2009), proteins (Fuda & Jauregi, 2006;Fuda, Bhatia, Pyle, & Jauregi, 2005) and polyphenols (MohdMaidin, Michael, Oruna-Concha, & Jauregi, 2017;Spigno, Dermiki, Pastori, Casanova, & Jauregi, 2010;Spigno, Amendola, Dahmoune, & Jauregi, 2015). The type of surfactant (i.e cationic, anionic and non-ionic) determines the outer charge of the CGA, where molecules with the opposite charge will attract to the CGA resulting in their effective separation into the CGA phase.…”
Section: Introductionmentioning
confidence: 99%
“…CGAs obtained from solutions of Tween20 surfactant at 1 mM, 10 mM, and 20 mM (200 mL), were characterized for stability in terms of gas hold up () and half-life (t 1/2 ) in the generation vessel (Jauregi and Dermiki, 2010). Higher surfactant concentrations were not tested since, as similarly reported by Dermiki et al (2010), no additional effects on CGAs structure were observed. For the experiments, freshly produced CGAs were transferred into a 500 mL volumetric cylinder and the volume of drained liquid was registered at regular time intervals within the range 0-25 min, until complete foam collapse.…”
Section: Characterization Of Cgasmentioning
confidence: 99%
“…Yeast has been currently suggested as an alternative for astaxanthin production because of its rapid growth rate, high biomass productivity, and health benefits (Ukibe et al, 2009;Freitas et al, 2014 b;Lin et al, 2017 b). Phaffia rhodozyma (Xanthophyllomyces dendrorhous) is a red-pigmented heterobasidiomycetous yeast, which has been extensively studied for astaxanthin production (Domínguez-Bocanegra et al, 2007;Dermiki et al, 2010;Stoklosa et al, 2018). However, low astaxanthin productivity in wild strain P. rhodozyma limits its industrial application (Fang and Cheng, 1993;Domínguez-Bocanegra et al, 2007;Liu et al, 2008;Montanti et al, 2011).…”
Section: Optimization Of Medium Compositions Using Rsmmentioning
confidence: 99%